Electrogenerated nickel(I) complexes as catalysts for the intramolecular radical cyclisation of unsaturated a-bromoesters - Duñach, E. (2004)
The indirect electroreduction of unsaturated α-bromoesters using Ni(II) complexes as electron-transfer mediators is achieved in N,N'-dimethylformamide by constant current electrolysis between a cathode and a sacrificial anode in a diaphragmless cell. Cyclic compounds are obtained in moderate to good yields in conditions that avoid the usual preparation using organotin reagents.